THE CORRELATION OF AUDIOVISUAL USAGE TOWARD LEVEL OF UNDERSTANDING AND STUDENT’S BEHAVIOR - Tony Susetyo; Adelina Hasyim; Hermi Yanzi (Jurnal Kultur Demokrasi, 2012)
The purpose of this research is to explain the correlation of audiovisual media usage toward student’s level of understanding and student’s behavior at seventh grade of SMP N 3 Batanghari Nuban Lampung Timur, Year of Study 2012/2013. The method used in this research is descriptive correlation method which uses whole students of seventh grade of SMP N 3 Batanghari Nuban , in amount of 131 people as the populations. There are 27 respondents as the sample. Data analysis uses chi quadrate with main technique of data collection uses questionnaire, test, and behavioral scale. The result shows that there are positive, significant, and intense relationship between audiovisual media usage and student’s  understanding, which means that the more optimal audiovisual media is being used the better student’s understanding will be and fortunately student’s behavior can be changed to be better, where at the end it helps the teaching learning activity to gain a better result.Keywords: audiovisual, tingkat pemahaman, sikap siswa.